Effect of Addition of Mimba Leaf Extract (Azadirachta Indica A. Juss) to Corn with Different Types of Packaging on Water Content, Percentage of Moldy Seeds, and Aflatoxin Levels - Santi, Mari; Montesqrit, Montesqrit; Harnentis, Harnentis (International Journal of Environment, Agriculture and Biotechnology, 2020)
This study was conducted to determine the effect of mimba leaf extract and the type of packaging on corn stored at 4 weeks. This study used an experimental method with Completely Randomized Design (CRD) consisting of 4 treatments, and each treatment was replicated with 4 times. The treatment was the types of packaging, consist of cartoon without cover, plastic sacks, paperboard, and vacuum plastic. The measured variables were water content, moldy seed percentage, and aflatoxin content in corn after stored. Results of this study showed that the effect of adding mimba leaf extract on all types of packaging significantly different (P<0.05) on moisture content, the percentage of moldy seeds, and the aflatoxin content. The conclusion was the adding of mimba leaf extract on all types of packaging can maintain moisture content, percentage of moldy seeds, and reduce the aflatoxin content.